2014
DOI: 10.1523/jneurosci.4773-13.2014
|View full text |Cite
|
Sign up to set email alerts
|

No Perisaccadic Mislocalization with Abruptly Cancelled Saccades

Abstract: Every saccadic eye movement that we make changes the image of the world on our retina. Yet, despite these retinal shifts, we still perceive our visual world to be stable. Efference copy from the oculomotor system to the visual system has been suggested to contribute to this stable percept, enabling the brain to anticipate the retinal image shifts by remapping the neural image. A psychophysical phenomenon that has been linked to this predictive remapping is the mislocalization of a stimulus flashed around the t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 43 publications
1
11
0
Order By: Relevance
“…Visual localization of briefly presented flashes is inaccurate around the onset of saccades; flashed targets are typically perceived as shifted in space toward the upcoming target of the saccade (Honda, 1995(Honda, , 2006Matin & Pearce, 1965;Ross, Morrone, Goldberg, & Burr, 2001). In line with Helmholtz's (1909) suggestion, the main, but not the only (Atsma, Maij, Corneil, & Medendorp, 2014), explanation for perisaccadic mislocalization is that the visual system makes use of the predictive efference copy of the eye movement (also known as corollary discharge; for review, see Wurtz, Joiner, & Berman, 2011). According to this hypothesis, the efference copy is used not only for accounting for the negative consequences of the saccadic eye movement on visual input, such as retinal smear, but also for actively preparing the visual system for the upcoming eye movement by changing its response properties.…”
Section: Introductionsupporting
confidence: 79%
“…Visual localization of briefly presented flashes is inaccurate around the onset of saccades; flashed targets are typically perceived as shifted in space toward the upcoming target of the saccade (Honda, 1995(Honda, , 2006Matin & Pearce, 1965;Ross, Morrone, Goldberg, & Burr, 2001). In line with Helmholtz's (1909) suggestion, the main, but not the only (Atsma, Maij, Corneil, & Medendorp, 2014), explanation for perisaccadic mislocalization is that the visual system makes use of the predictive efference copy of the eye movement (also known as corollary discharge; for review, see Wurtz, Joiner, & Berman, 2011). According to this hypothesis, the efference copy is used not only for accounting for the negative consequences of the saccadic eye movement on visual input, such as retinal smear, but also for actively preparing the visual system for the upcoming eye movement by changing its response properties.…”
Section: Introductionsupporting
confidence: 79%
“…PS at location 2,24,12,26,27,and 5;26,11,22,26,and 7;31,12,26,25,and 5. PS at location three,28,35,32,25,and 6;24,13,27,26,and 7;32,14,28,25,and 7. under quite different conditions, in which participants were asked either to maintain fixation (Dorr & Bex, 2013;Ostendorf et al, 2006) or to cancel eye movements (Atsma et al, 2014). There are obviously a number of differences between making a saccade and not making one, such as the tight temporal and spatial link between attention and the saccade target.…”
Section: Discussionmentioning
confidence: 99%
“…The authors showed that it was possible to reduce visual sensitivity by shifting the visual input while participants were maintaining fixation, suggesting that the main role was played by the retinal speed rather than the extraretinal signal. Atsma, Maij, Corneil, and Medendorp (2014) recently reported that canceling a saccade reduces mislocalization, suggesting that the eye movement itself is a necessary prerequisite to mislocalize a probe stimulus.…”
Section: Introductionmentioning
confidence: 99%
“…Zimmermann, Born, Fink, and Cavanagh (2014) have shown that perceptual mislocalization can be induced by a peripherally presented, attentiongrabbing stimulus followed by an uncertainty inducing backward mask. Conversely, Atsma, Maij, Corneil, and Medendorp (2014) have shown that stimuli are more accurately localized if a saccade is planned and then not executed during a go/no-go task. In the first study there is a clear disruption via the backward mask but it may appear that there is no motor plan.…”
Section: Introductionmentioning
confidence: 98%